2011
DOI: 10.5114/aoms.2011.23416
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breast-feeding duration on bone mineral density in postmenopausal Turkish women: a population-based study

Abstract: IntroductionIn the present study, we investigated the effects of breast-feeding time on bone mineral density (BMD) later in life.Material and methodsThe current study was based on a retrospective analysis of 586 postmenopausal women with a mean age of 60.8 years, who were screened for osteoporosis by dual energy X-ray absorptiometry (DXA).They were classified into 4 groups with respect to the duration of their breast-feeding as never (group 1), 1-24 months (group 2), 25-60 months (group 3), or > 60 months (gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
3
16
0
7
Order By: Relevance
“…Moreover, they reported that lumbar and femoral neck BMD of female patients with longer lactation periods were lower than those of female patients with shorter lactation periods. Similar results were also demonstrated in other studies (30,31) In the light of the available data, the relationship between pregnancy and bone mass is complicated and it still remains unclear. Theoretically, bone mass may decrease during pregnancy because of the requirement of calcium during pregnancy.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, they reported that lumbar and femoral neck BMD of female patients with longer lactation periods were lower than those of female patients with shorter lactation periods. Similar results were also demonstrated in other studies (30,31) In the light of the available data, the relationship between pregnancy and bone mass is complicated and it still remains unclear. Theoretically, bone mass may decrease during pregnancy because of the requirement of calcium during pregnancy.…”
Section: Discussionsupporting
confidence: 77%
“…18 In a recent study, Wiklund et al displayed the protective effect of lactation on bone size and strength in direct correlation with its duration while Yazici et al found no effect of lactation and its duration on postmenopausal women. 19,20 Kauppi et al also confirmed the positive effect of parity on BMD and showed inverse association between risk of hip fracture and parity. 21 Moller et al concluded in their study that pregnancy and breastfeeding cause a reversible bone loss.…”
Section: Discussionmentioning
confidence: 61%
“…Many studies have shown the association between breastfeeding and osteoporosis . However, the results are conflicting , some studies found no association between breastfeeding and osteoporosis later in life (5,6), in contrast, some studies show that breastfeeding history is associated with an increased Bone Mineral Density. (7).…”
Section: Introductionmentioning
confidence: 72%